iStent® Trabecular Microbypass Stent: An Update - Arthur Fernandes Resende; Neal Sanjay Patel; Michael Waisbourd; L. Jay Katz (Journal of Ophthalmology)
Due to the high rates of complications and failure experienced with current glaucoma procedures, there is a continuous search for a safer and more effective glaucoma surgery. A new class of procedures termed minimally invasive glaucoma surgeries (MIGS) aim to fill this void by offering an alternative method of IOP reduction associated with markedly reduced complication rates and shorter recovery times. The iStent, a trabecular microbypass stent, is a MIGS device that has quickly gained popularity. The device allows aqueous humor to directly drain from the anterior chamber into Schlemm’s canal by bypassing an obstructed trabecular meshwork. This review examines publications about the iStent, focusing on the device’s efficacy, safety, and cost when a single iStent or multiple iStents are implanted in combination with cataract surgery or as a solo procedure. Current data suggest that the iStent is a safe and effective tool in the management of mild-to-moderate glaucoma, notable for its limited complications and absence of serious adverse events following implantation. As valuable experience is gained performing ab interno MIGS, increasing familiarity with angle anatomy and iStent placement, and as newer stent designs are developed, there is promise of continual improvement in the surgical management of glaucoma.